Theoretical, methodological and terminological issues in researching indirect translation: A critical annotated bibliography - Pięta, Hanna (2017)
This is a critical annotated bibliography of publications on theoretical, methodological and terminological issues raised by the specific nature of research on indirect translation. It covers 19 bibliographic items (book chapters and journal articles). Each bibliographic entry is accompanied by a critical annotation summarizing the central theme of the selected publication and foregrounding its noteworthy contributions with regard to indirect translation theory, methodology and metalanguage. An introduction to the bibliography explains how the bibliographic items were located and selected. It also identifies key patterns that emerge from a brief bibliometric study of the publications collected thus far. An appendix to the bibliography contains an extensive listing of publications focused primarily on indirect translation, from which the bibliography was selected. It is hoped that both the bibliography and the appendix will provide a useful springboard for future research in the field.